ENERGI, KARBOHIDRAT, SERAT, DAN AKTIVITAS FISIK: KONTRIBUTOR KEGEMUKAN PADA SISWA SMA - Sholihah, Siti Nurbayani; Judiono, Judiono; Saleky, Yohannes Willihelm; Rahmat, Mamat; Pusparini, Pusparini; Suprihartono, Fred Agung; Fauziyah, Raden Roro Nur (Poltekkes Kemenkes Bandung, 2024)
Obesity is a condition resulting from an imbalance between energy intake and expenditure, leading to excess energy stored as fat tissue. Factor contributing to obesity in adolescents primary stem from dietary patterns. This study aims to determine the relationship between energy intake, carbohydrate intake, fiber intake, physical activity, and obesity among 11th-grade students at SMA Negeri 1 Ngamprah, West Bandung Regency. A cross-sectional research design was employed, with a sample size of 48 students with random sampling. The sampling technique used was random sampling. Data collection involved interviews, questionnaires, and measurements of weight and height. The data was analyzed using Chi-square and logistic regression tests. The findings revealed that 26 students (54,2%) were obese, while only 2,1% met the daily fiber requirements. Significant relationships were found between energy intake (p=0,000), carbohydrate intake (p=0,000), and physical activity (p=0,003) with obesity. However, no significant association was found between fiber intake and obesity (p = 1,000). The variable that significantly influenced obesity was energy intake (p = 0,008; OR = 24,227; CI: 2,339-250,902), while carbohydrate intake (p = 0,076; OR = 4,837; CI: 0,848-27,597) and physical activity (p = 0,367; OR = 2,274; CI: 0,381-13,556) do not directly influenced obesity. Enhancing students’ understanding and behaviors regarding balanced nutrition, along with boosting physical activity through extracurricular activities, is necessary to reduce obesity among adolescents.